2009
DOI: 10.5455/vetworld.2009.15-16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Haemoprotozoan diseases in crossbred cattle in banglore north

Abstract: The prevalence of haemoprotozoan disease in crossbred cattle was studied by screening 132 clinically suspected blood samples by Geimsa's stained blood smear method. Among 132 crossbred cattle screened, 57 animals were found positive for haemoprotozoan parasites. Out of 57 positive cases, 41 were found positive for Theileria annulata and the remaining 16 were positive for Babesia bibemina. The highest prevalence was found in 4-6 year age group and in monsoon months. The hematological observation revealed reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 2 publications
16
38
1
Order By: Relevance
“…Out of 215 cattle and 85 buffaloes screened, 110 (51.1 %) and 20 (23.5 %) were found positive for haemoprotozoan infections respectively. This finding is in agreement with Ananda et al (2009) who reported almost similar overall prevalence of 43.1 % in crossbred cattle from Bangalore region of Karnataka.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Out of 215 cattle and 85 buffaloes screened, 110 (51.1 %) and 20 (23.5 %) were found positive for haemoprotozoan infections respectively. This finding is in agreement with Ananda et al (2009) who reported almost similar overall prevalence of 43.1 % in crossbred cattle from Bangalore region of Karnataka.…”
Section: Resultssupporting
confidence: 82%
“…This is in accordance with the observation made by Vahora et al (2012), Radostits et al (1994), Roy et al (2004), Ananda et al (2009Ananda et al ( , 2014 who have reported the highest prevalence of haemoprotozoan infection in monsoon months. The reason may be due to high abundance of vector population during the monsoon season as compared to other seasons in a year.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Our observations correlate with the results of previous studies on incidence of haemoprotozoan parasites in bovines. (Roy et al, 2004;Ananda et al, 2009Ananda et al, , 2014Sharma et al, 2015 a & b). In the present study, highest incidence of B. bigemina infection was recorded in both cattle and buffaloes.…”
Section: Resultsmentioning
confidence: 99%
“…Constant exposure of infections and development of immunity against such infections might be responsible for lower prevalence in indigenous cattle (Siddiki et al, 2010). On the contrary, more attention in the management of crossbred cattle gives less chance of pre-exposure of vectors and develops no or less immunity, resulting frequent occurrence of such diseases (Ananda et al, 2009;Chowdhury et al, 2006;Siddiki et al, 2010). Age also influences the occurrence of Babesia and Anaplasma infections.…”
Section: Breedmentioning
confidence: 99%